2021
DOI: 10.3390/joitmc7040240
|View full text |Cite
|
Sign up to set email alerts
|

Product Quality Planning in Laser Metal Processing Based on Open Innovation Using Quality Function Deployment

Abstract: The results of the development of a modified quality function deployment (QFD) method, obtained for the first time to improve the product quality planning process in the metal cutting of laser technologies confirming the dynamics of open innovation, are presented. When using new marketing technologies, the requirements of consumers are established; a factorial model of customer satisfaction was determined with after an assessment by expert methods, their wishes were transformed into indicators of product quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…'Industry 4.0', 'Integrated Industry', or 'Smart factory' that can uphold the entire product life cycle from designing an article to its delivery are commonly used technical terms (Hofmann and Rüsch 2017). The world is struggling to cope with emerging technologies, dynamic processes, novel terminologies (Syreyshchikova et al 2021b;Tayal et al 2021), and intense competition in terms of service and quality (Tripathi et al 2021a). On the same grounds, Indian manufacturing organizations find it challenging to adapt to changing customer needs these days.…”
Section: Introductionmentioning
confidence: 99%
“…'Industry 4.0', 'Integrated Industry', or 'Smart factory' that can uphold the entire product life cycle from designing an article to its delivery are commonly used technical terms (Hofmann and Rüsch 2017). The world is struggling to cope with emerging technologies, dynamic processes, novel terminologies (Syreyshchikova et al 2021b;Tayal et al 2021), and intense competition in terms of service and quality (Tripathi et al 2021a). On the same grounds, Indian manufacturing organizations find it challenging to adapt to changing customer needs these days.…”
Section: Introductionmentioning
confidence: 99%
“…This activity points to a forward insightful understanding of how enterprises deliberately utilize electronic innovation and data frameworks to play down carbon outflows for supportability. Syreyshchikova et al (2021) clarify the perplexing relationship between extended course and complexity, which influences these arrangements. This investigation makes a difference in firms selecting carbon-reducing IT and etech arrangements.…”
Section: Introductionmentioning
confidence: 92%
“…Hina, Hassan, Parveen, and Arooj (2021) found that project-focused cultures benefit from transformational leadership, which emphasizes inspiration, empowerment, and vision. Project managers need good interpersonal and communication skills and knowledge of project management processes and technology (Syreyshchikova et al, 2021). Agile, waterfall, and hybrid project management models are also important.…”
Section: Project Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…The QFD method systematically determines consumer demands and then translates the needs into appropriate product planning (Yan et al, 2022). Research has developed products using the QFD method to create products, such as UMS garbage bins (Musthofa et al, 2015), electric batik stoves (Lestariningsih & Jono, 2019), tempeh chips (Rohmah et al, 2018), clotheslines (Wibowo & Purnomo, 2017), laser metal processing based on open innovation (Syreyshchikova et al, 2021), and integrated multiphase sustainable product design (Ocampo et al, 2020). Research on developing traditional market garbage bin bins with the QFD method has never been done.…”
Section: Introductionmentioning
confidence: 99%